2009
DOI: 10.1016/s1808-8694(15)30557-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cigarette smoking on the respiratory epithelium and its role in the pathogenesis of chronic rhinosinusitis

Abstract: Although there is evidence supporting a link between smoking and CRS, studies suggest that there might be individual susceptibility to cigarette smoking causing the development and/or maintenance of CRS. Proper patient education to quit smoking as well as reinforcement of antismoking campaigns are extremely important to control this disease of major socio-economic impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 32 publications
(22 reference statements)
2
25
1
1
Order By: Relevance
“…One may hypothesize that tobacco smoke impairs sinonasal mucosal healing through decreased mucociliary clearance, and ongoing inflammation after MIER . Multiple studies have demonstrated that smoking negatively impacts surgical outcomes, symptom scores, patient‐reported outcomes, and QOL improvements in smokers vs nonsmokers in patients undergoing endoscopic sinus surgery for chronic sinusitis . The present data from endoscopic skull‐base surgery appears to follow the same dictum.…”
Section: Discussionsupporting
confidence: 55%
“…One may hypothesize that tobacco smoke impairs sinonasal mucosal healing through decreased mucociliary clearance, and ongoing inflammation after MIER . Multiple studies have demonstrated that smoking negatively impacts surgical outcomes, symptom scores, patient‐reported outcomes, and QOL improvements in smokers vs nonsmokers in patients undergoing endoscopic sinus surgery for chronic sinusitis . The present data from endoscopic skull‐base surgery appears to follow the same dictum.…”
Section: Discussionsupporting
confidence: 55%
“…A limited number of prior nonsystematic reviews have focused on smoking and CRS . Only 1 review has investigated the association between SHS and CRS.…”
Section: Discussionmentioning
confidence: 99%
“…Cotinine, a nicotine metabolite, has been associated with inducing ciliary dysfunction, affecting mucociliary transport in the middle ear . Smoking also increases mucous production through an augmented proliferation of goblet cells in the respiratory mucosa . Therefore, the combination of ciliary dysfunction and increased mucous production creates a plausible pathophysiologic explanation for a causal relationship between SHS and sinusitis.…”
Section: Discussionmentioning
confidence: 99%
“…24 Images were then loaded into ImageJ software, and the ciliated areas were delimited, measured, and compared with the total area. The average values and SDs of percentage ciliation of the representative SEM images were calculated.…”
Section: Quantification Of Ciliated Coveragementioning
confidence: 99%